1989
DOI: 10.1111/j.1365-2044.1989.tb11446.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison between open‐end (single hole) and closed‐end (three lateral holes) epidural catheters

Abstract: Summary

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
1

Year Published

1993
1993
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(32 citation statements)
references
References 6 publications
3
28
1
Order By: Relevance
“…Aspiration of blood through the epidural catheter immediately following insertion was classified as a bloody tap and was often associated with a definite click on catheter insertion. The incidence was similar with both catheter types (6.5%), and was lower than that recorded in previous work with multiholed catheters, but higher than the findings for singleholed catheters [2,3]. Small volumes of altered blood were aspirated on four occasions just prior to top-up, twice in each group, but no constant flow of blood was obtained at this time.…”
Section: Minor Complicationssupporting
confidence: 69%
See 4 more Smart Citations
“…Aspiration of blood through the epidural catheter immediately following insertion was classified as a bloody tap and was often associated with a definite click on catheter insertion. The incidence was similar with both catheter types (6.5%), and was lower than that recorded in previous work with multiholed catheters, but higher than the findings for singleholed catheters [2,3]. Small volumes of altered blood were aspirated on four occasions just prior to top-up, twice in each group, but no constant flow of blood was obtained at this time.…”
Section: Minor Complicationssupporting
confidence: 69%
“…There was no significant difference between the groups in the reported incidence of unsatisfactory blocks (6%), with unilateral blocks being commoner than missed segments, as in previous studies, where the frequency of unsatisfactory blocks has been reported as 14% and 21% [2,3]. Four catheters required resiting, an incidence of 1 % compared to 3% and 6% in other studies [2,3].…”
Section: Quality Of Blocksupporting
confidence: 45%
See 3 more Smart Citations